2011
DOI: 10.1002/ajmg.b.31192
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation of the serotonin receptor type‐2A Gene (HTR2A) at T102C polymorphic site in DNA derived from the saliva of patients with schizophrenia and bipolar disorder

Abstract: Several lines of evidence indicate that dysfunction of serotonin signaling and HTR2A receptor are involved in the pathogenesis of schizophrenia (SCZ) and bipolar disorder (BD). DNA methylation of HTR2A at T102C polymorphic site influences HTR2A expression and aberrant DNA methylation of HTR2A promoter was reported in postmortem brain of patients with SCZ and BD. Hypothesizing that the brain's epigenetic alteration of HTR2A may also exist in peripheral tissues that can be used as a diagnostic/therapeutic biomar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
74
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 45 publications
9
74
0
2
Order By: Relevance
“…Note that the T102C SNP in the HTR2A gene is part of a methylation site that influences the expression of this serotonin receptor. Therefore, some of the discrepant findings concerning the association of this SNP with FMS (see Table 5) may arise from differential methylation and gene expression in carriers of the C allele [478]. In a pilot study, it was recently shown that the genome-wide methylation pattern differed significantly between women with FMS and healthy controls [479].…”
Section: Epigeneticsmentioning
confidence: 99%
“…Note that the T102C SNP in the HTR2A gene is part of a methylation site that influences the expression of this serotonin receptor. Therefore, some of the discrepant findings concerning the association of this SNP with FMS (see Table 5) may arise from differential methylation and gene expression in carriers of the C allele [478]. In a pilot study, it was recently shown that the genome-wide methylation pattern differed significantly between women with FMS and healthy controls [479].…”
Section: Epigeneticsmentioning
confidence: 99%
“…A handful of studies were epidemiological (e.g. Nazarova, 1996), whilst others used methods including saliva samples (Ghadirivasfi et al, 2011), GWAS and and not available to the same degree across subjects -D. A. Lewis, 2002).…”
Section: Empirical Research With Humansmentioning
confidence: 99%
“…Benes et al, 2007;Carrard, Salzmann, Malafosse, & Karege, 2011;Ghadirivasfi et al, 2011). Others investigated brain features such as cerebellar weight and pre-frontal cortex variations, levels of methylation in brain or blood tissues, associations between epigenetic processes and smoking, age, medication use and physical activity, studies of x-chromosome linkage, and paternal age and its association with schizophrenia diagnoses (e.g.…”
Section: Empirical Research With Humansmentioning
confidence: 99%
“…Polymorphisms in the genes encoding these receptors are considered good candidates for mediating susceptibility to psychosis, and they have been widely studied in genetic association studies [4]. Recently, increasing emphasis has been placed on the potential role of epigenetic dysfunction in the etiology of psychosis [5,6], and converging evidence suggests that epigenetic factors are important in the regulation of serotonin receptor gene expression [7][8][9].…”
Section: News and Views News And Views News And Viewsmentioning
confidence: 99%